Optimalisasi Pengelolaan Usaha melalui Pendampingan Berbasis Praktik pada “Seafood Gemgal” - Ririn Uke Saraswati; Sri Winda Hardiyanti Damanik; Soedjatmoko Soedjatmoko; Ranuyoga Arsyiandi; Sarmin Sarmin; Oggie Recksadithia; Dany Prio Hutomo; Suripto Moh. Zulkifli; Hanna Hanifah (Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in coastal areas have significant potential to contribute to local economic growth; however, they often face limitations in business management practices. This community service activity aims to optimize business management through practice-based mentoring at Seafood “Gemgal” located in Muara Gembong. The main problems identified include the absence of systematic financial recording, conventional promotional strategies, unattractive business banner design, and the lack of written Standard Operating Procedures (SOPs) for service delivery. The implementation method consisted of initial observation, SWOT analysis, strategy formulation, mentoring implementation, and evaluation of pre- and post-activity achievements. The results demonstrate significant improvements in managerial capacity, evidenced by the implementation of daily financial bookkeeping, redesign of a more professional and visually appealing business banner, utilization of social media for marketing purposes, and the development of simple service SOPs. Practice-based mentoring proved effective as it enabled direct application of structured business management principles. This mentoring model can be replicated among other coastal MSMEs to enhance competitiveness and long-term business sustainability.